Response gene to complement-32 promotes cell survival via the NF-κB pathway in non-small-cell lung cancer - Zhang, Jing (Exp Ther Med, 2020)
Response gene to complement (RGC)-32 regulates the cell cycle in response to complement activation. The present study demonstrated that the expression level of RGC-32 is higher in human non-small-cell lung cancer (NSCLC) tissues compared with health controls. Overexpressing RGC-32 induced p65 nucleus translocation, significantly increased nuclear p65 levels and promoted the proliferation of A549 cells. Knockdown of RGC-32 by short hairpin RNA decreased the expression level of nuclear p65 and inhibited cell proliferation. The increase in cell proliferation induced by RGC32 could be abolished by the NF-κB inhibitor pyrrolidine dithiocarbamate. Mechanistic studies indicated that RGC32 mediated NF-κB downstream genes, including vascular cell adhesion protein 1, interleukin-6, cyclin dependent kinase inhibitor 2C, testin and vascular endothelial growth factor A. In summary, the present study demonstrated a novel role of RGC-32 in the progression of NSCLC via the NF-κB pathway and p65. Therefore, RGC-32 could be a potential therapeutic target for NSCLC.